1971
DOI: 10.1007/bf02545733
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the extent of rancidity of soybean oil by gas chromatography compared with peroxide value

Abstract: The development of rancidity in soybean oil has been studied by gas chromatography (GC), peroxide value (PV) and sensory evaluation. The GC method has been adapted from previous methodology and another type of column packing has been used for the purpose. The GC peaks have been treated as one whole group, and and oxidation value (OV) has been computed by means of an internal standard (n‐octanol). The OV’ have been correlated with the PV’s. The flavor of soybean oil and a blend of 50% soybean oil and 50% hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…Peroxide levels increased over storage time matching previously reported soybean rancidity studies [31,32]. Interestingly, canola oil (from 3 to 66 meq/kg) showed the highest oxidative stability while corn (from 1 to 105 meq/kg) and cottonseed oil (from 3 to 106 meq/kg) had the highest rate of peroxide formation at the end of 30 days.…”
Section: Monitoring Oxidative Parameters In Vegetable Oilssupporting
confidence: 81%
“…Peroxide levels increased over storage time matching previously reported soybean rancidity studies [31,32]. Interestingly, canola oil (from 3 to 66 meq/kg) showed the highest oxidative stability while corn (from 1 to 105 meq/kg) and cottonseed oil (from 3 to 106 meq/kg) had the highest rate of peroxide formation at the end of 30 days.…”
Section: Monitoring Oxidative Parameters In Vegetable Oilssupporting
confidence: 81%
“…Pen-tane evolved from peroxides during their decomposition has been corre lated with rancidity [34,35], and studies of pentane formation in foods have shown that it is possible to correlate linoleate content and iodine values with the induction period for pentane formation [36]. Pen-tane evolved from peroxides during their decomposition has been corre lated with rancidity [34,35], and studies of pentane formation in foods have shown that it is possible to correlate linoleate content and iodine values with the induction period for pentane formation [36].…”
Section: Pentane In Breath As a Measure Of In Vivo Lipid Peroxidmentioning
confidence: 99%
“…Pentane formation was unusually fast for this sample in comparison with the others. Evans et al (1969) and Jarvi et al (1971) found correlations between pen tane and flavor scores and between pentane and peroxide values. These oils were directly injected on a GC column.…”
Section: Resultsmentioning
confidence: 98%
“…Evans et al (1967) reported that pentane is the predominant short-chain hydrocarbon to arise through thermal decomposition. Correlations of flavor scores and pentane formation have been used to determine rancidity of oils after directly injecting the oils o n a GC column (Evans e t al., 1969;Jarvi et al, 1971). But deterioration studies of solid foods require analysis of headspace gases.…”
Section: Introductionmentioning
confidence: 99%